2013
DOI: 10.1093/eurheartj/eht018
|View full text |Cite
|
Sign up to set email alerts
|

The hibernating myocardium: current concepts, diagnostic dilemmas, and clinical challenges in the post-STICH era

Abstract: A very large body of evidence--predominantly retrospective--suggests that revascularization is superior to optimal medical therapy in patients with a significant amount of 'hibernating' myocardium. Contemporary cardiological practice has embraced this standard of practice, as many centres worldwide place great emphasis upon the results of viability testing by non-invasive imaging techniques in determining the need for coronary revascularization. This practice has been challenged by the recent results of the Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
21

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 81 publications
(71 reference statements)
1
57
0
21
Order By: Relevance
“…28,29 Left ventricular ejection fraction (eg, ≤30%) is currently one of the major means for stratifying risk, for example, for predicting the development of sudden cardiac death. 30 However, a considerable number of patients with left ventricular ejection fraction >30% still suffer sudden cardiac death, and the consequence of classifying a high number of patients falsely as being at high risk is exerting pressure on our healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Left ventricular ejection fraction (eg, ≤30%) is currently one of the major means for stratifying risk, for example, for predicting the development of sudden cardiac death. 30 However, a considerable number of patients with left ventricular ejection fraction >30% still suffer sudden cardiac death, and the consequence of classifying a high number of patients falsely as being at high risk is exerting pressure on our healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…The final remodeling phase is characterized by fibrosis and LV dilatation (29,51,67). Recent clinical studies involving cardiac MRI have indicated that the amount of scarring in the thinned region of the heart inversely correlates with the improvement of regional and global systolic function after revascularization of such chronic ischemic areas (65), indicating that, in particular, the nonfibrotic tissue may consist of hibernating myocytes that become revitalized and functional upon the restoration of blood flow (64). In fact, regional wall thinning can be reversible upon revascularization, presumably by the reversal of hibernation, and this reverse remodeling is associated with a favorable prognosis in patients after MI (9,65).…”
Section: Our Data Provide New Insights Into the Exercise-mediated Carmentioning
confidence: 99%
“…Scars < 50% and > 75% have a high and low probability of functional recovery, respectively. 21 Although many studies point to the benefit of resonance and described tests in the management of ischemic cardiomyopathy, the lack of randomized controlled trials with hard clinical endpoints has not yet established the routine use of these methods in clinical practice.…”
Section: Echocardiographymentioning
confidence: 99%